Phlebosclerosis in lower extremities veins. (April 2014) - Labropoulos, N; Tzogias, L; Malgor, R D; Antoniou, G; Giannoukas, A D
Objectives: To determine the prevalence, distribution and extent of phlebosclerosis in an outpatient population referred to vascular clinic. Design: Prospective cohort study. Patients and Methods: Seven hundred and forty consecutive patients, 302 (41%) men with a cohort median age of 49 (range, 18–84), were referred to the vascular clinic for detection of lower extremity acute or chronic venous disease. A total of 1000 limbs were assessed using duplex ultrasonography. Deep veins were not assessed. Characteristics of venous wall and lumen were studied. Phlebosclerosis was diagnosed based on the increased echogenicity and thickness or calcification of the venous wall. Patients with known trauma or any surgery in the lower extremities were excluded. Two control groups were used for comparison, one of consecutive patients undergoing vein mapping ( n = 100) and the other of younger volunteers free of any vein disease ( n = 25). Results: Of the 1000 limbs (right: 458, left: 542) studied by duplex ultrasound, 21 limbs had intense brightness of the venous wall. Fifteen of them had also calcifications and 61 wall thickening. The prevalence of phlebosclerosis was significantly higher in the patient group when compared with control groups 1 (P = 0.019) and 2 (P = 0.011). The mean age of patients with phlebosclerosis was higher compared with the whole patient group (57 versus 49 years, P < 0.0001). Phlebosclerosis affected all superficial veins with greater prevalence in the small saphenous vein (SSV). The mean length of the phlebosclerotic lesion was 2 cm (range 1–7 cm). Conclusion: The prevalence of phlebosclerosis in the lower extremities appears to be low with no significant sex differences. Age and chronic venous disease are important factors for its development. It may be present in the absence of thrombosis or reflux. A greater prevalence of phlebosclerotic lesions was found in the SSV.